Interaction between Multimeric von Willebrand Factor and Complement: A Fresh Look to the Pathophysiology of Microvascular Thrombosis - Serena Bettoni; Miriam Galbusera; Sara Gastoldi; Roberta Donadelli; Chiara Tentori; Giuseppina Spartà; Elena Bresin; Caterina Mele; Marta Alberti; Agustín Tortajada; Hugo Yébenes; Giuseppe Remuzzi; et al. (2017)
Abstract von Willebrand factor (VWF), a multimeric protein with a central role in hemostasis, has been shown to interact with complement components. However, results are contrasting and inconclusive. By studying 20 patients with congenital thrombotic thrombocytopenic purpura (cTTP) who cannot cleave VWF multimers because of genetic ADAMTS13 deficiency, we investigated the mechanism through which VWF modulates complement and its pathophysiological implications for human diseases. Using assays of ex vivo serum-induced C3 and C5b-9 deposits on endothelial cells, we documented that in cTTP, complement is activated via the alternative pathway (AP) on the cell surface. This abnormality was corrected by restoring ADAMTS13 activity in cTTP serum, which prevented VWF multimer accumulation on endothelial cells, or by an anti-VWF Ab. In mechanistic studies we found that VWF interacts with C3b through its three type A domains and initiates AP activation, although assembly of active C5 convertase and formation of the terminal complement products C5a and C5b-9 occur only on the VWF-A2 domain. Finally, we documented that in the condition of ADAMTS13 deficiency, VWF-mediated formation of terminal complement products, particularly C5a, alters the endothelial antithrombogenic properties and induces microvascular thrombosis in a perfusion system. Altogether, the results demonstrated that VWF provides a platform for the activation of the AP of complement, which profoundly alters the phenotype of microvascular endothelial cells. These findings link hemostasis-thrombosis with the AP of complement and open new therapeutic perspectives in cTTP and in general in thrombotic and inflammatory disorders associated with endothelium perturbation, VWF release, and complement activation.